MODERN SOLUTIONS TO ENVIRONMENTAL PROBLEMS IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Environmental issues in Uzbekistan are gaining increasing significance due to rapid industrial development, population growth, and climate change. The article examines the main environmental threats, including soil degradation, water scarcity, air pollution, and loss of biodiversity. It analyzes current national and international strategic solutions aimed at minimizing the negative impacts of economic activities. The primary focus is on projects for the restoration of the Aral Sea, programs for sustainable water resource management, development of "green" energy, waste management, and improving environmental awareness among the population. The study employs methods of official statistics analysis, comparative analysis of environmental programs, and case studies of successful initiatives. The achievements, limitations, and prospects of Uzbekistan's environmental policy are discussed. The author concludes that effectively addressing environmental problems requires a comprehensive approach, active participation from society and businesses, and the implementation of innovative technologies.